2016
DOI: 10.3847/2041-8205/818/1/l7
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Photometry of the Disintegrating Planetesimals at Wd1145+017: Evidence for Rapid Dynamical Evolution

Abstract: We obtained high-speed photometry of the disintegrating planetesimals orbiting the white dwarf WD 1145+017, spanning a period of four weeks. The light curves show a dramatic evolution of the system since the first observations obtained about seven months ago. Multiple transit events are detected in every light curve, which have varying durations (;3-12 minutes) and depths (;10%-60%). The time-averaged extinction is ;11%, much higher than at the time of the Kepler observations. The shortest-duration transits re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 44 publications
6
146
1
1
Order By: Relevance
“…Subsequent passes further degrade the debris and it eventually embodies a disc geometry. Vanderburg et al (2015) have recently identified the first disintegrating asteroid around the dusty WD 1145+017 (see also Gänsicke et al 2016;Rappaport et al 2016), providing support to this interpretation. The signature of a disc orbiting a WD is excess emission in the infrared due to the reprocessed light from this dust.…”
Section: Introductionmentioning
confidence: 57%
“…Subsequent passes further degrade the debris and it eventually embodies a disc geometry. Vanderburg et al (2015) have recently identified the first disintegrating asteroid around the dusty WD 1145+017 (see also Gänsicke et al 2016;Rappaport et al 2016), providing support to this interpretation. The signature of a disc orbiting a WD is excess emission in the infrared due to the reprocessed light from this dust.…”
Section: Introductionmentioning
confidence: 57%
“…Previous observation-based analyses suggested that WD 1145+017 may be currently accreting at a rate significantly higher than inferred to be ongoing for any polluted white dwarf, and up to 10 12 g s −1 (Xu et al 2016;Gänsicke et al 2016;Rappaport et al 2016). This rate is ∼ 10 2 times higher than the steady-state inference from the heavy elements in the stellar atmosphere, and ∼ 10 3 times higher than any instantaneous rate inferred via a steady-state regime calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Vanderburg et al (2015) have identified a cloud of debris in uri.mal@tx.technion.ac.il˜˜˜˜hperets@physics.technion.ac.il the process of disintegrating (Gaensicke et al 2015;Xu et al 2016). …”
Section: Introductionmentioning
confidence: 99%